Design and Construction of an IoT-Based Automatic Fish Feeder Using Telegram Bot - Roihan, Ahmad; Rafika, Ageng Setiani; Andriyansah, Andriyansah; Rahayu, Sri (UNIVERSITAS RAHARJA, 2025)
This research presents the design and development of an automatic fish feeder based on the Internet of Things (IoT), integrated with the Telegram application. The device is intended to assist fish farmers, particularly those farming catfish, in feeding their fish automatically or remotely while away. The research adopts the Research and Development (R&D) method, utilizing the Software Development Life Cycle (SDLC) Waterfall model in the system development process. The stages include requirement analysis, system design, implementation, testing, and maintenance. The system is capable of dispensing feed automatically based on a predefined schedule using an RTC module, and it enables control and monitoring through commands sent via a Telegram bot. Testing results indicate that the system operates effectively, enhancing the efficiency and accuracy of fish feeding. The implementation of this device is expected to serve as an innovative solution to support productivity and sustainability in modern catfish farming practices.